MENINGKATKAN HASIL BELAJAR IPA MELALUI VIDEO PEMBELAJARAN ANIMASI BERBASIS ZOOM MEETING DI MASA PANDEMI VIRUS COVID-19 (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kuningan, 2023)
This study is a Classroom Action Research (CAR) that implements the animated video learning media model based on Zoom meetings to enhance the learning outcomes of Natural Sciences (IPA). Animated video learning is an instructional media that can be used in Zoom-based learning activities or to understand learning concepts. The problem addressed is the improvement of learning outcomes in Natural Sciences for grade 5 students at SD PLUS AL-MU’AAWANAH Ciamis. The research consists of two cycles, each comprising four stages: Planning, Implementation, Observation, and Reflection. The study involves 35 students, including 15 female students and 20 male students. In the pre-cycle phase, the learning mastery percentage was 25.71%. After implementing the first cycle of learning using PowerPoint media via Zoom meetings, there was an increase in the learning mastery percentage to 71.43%. In the second cycle, the learning mastery percentage reached 100%. The research results indicate an improvement in students' learning outcomes with the application of animated video learning media through Zoom meetings. Therefore, the research demonstrates that the implementation of animated video learning media based on Zoom meetings can enhance the learning outcomes of Natural Sciences for grade 5 students at SD PLUS AL-MU’AAWANAH Ciamis.